When one country's land gain is another country's land loss...: The social, ecological and economic dimensions of sand extraction in the context of world-systems analysis exemplified by Singapore's sand imports - Maria Franke (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
Singapore industrialised rapidly with continuously high growth rates since its independence in 1965 and its population during the same period of time almost tripled. With development at this scale, Singapore had to grow in number of industrial and residential buildings as well as in size through land reclamations; both requiring high amounts of sand. The country itself contains hardly any natural resources and, consequently, depends highly on other countries (mainly Malaysia, Indonesia, Cambodia and Vietnam) for its sand supply. All major sand supplying countries successively prohibited sand exports to Singapore beginning in 1997, since they were burdened with the social and economic costs that resulted from sand extraction. World-systems theory helps to explain the sand situation within the framework of the core/periphery hierarchy and the zero-sum game world-systems approach by arguing that Singapore, being an upper semi-peripheral country, could develop rapidly at the expense of the other countries which are found below Singapore in the core/periphery concept. Furthermore, it is shown that Singapore's resource strategy of importing large quantities of sand has helped its upward movement from a peripheral to an upper semi-peripheral country.
Keywords: F18; L72; P10; Q34; 330; world-systems theory; Singapore; sand extraction; sand export bans